Boron removal from scheduled waste leachate using hybrid adsorption-membrane system augmented with TiO₂ nanoparticles - Umar, Abba Mohammed (2021)
Landfilling is the most widely adopted waste disposal technique in most countries across the globe due to its simplicity among other waste disposal methods. However, the production of extremely polluted leachate containing boron from landfill has caused a great deal of concern due to high concentration which is toxic and harmful to the environment. Several treatment technologies including, adsorption, electrocoagulation, chemical coagulation, chemical precipitation and membrane have been reported in eliminating boron from a generated effluent before discharge. However, the application of these methods is being limited by some drawbacks. Low adsorption ability, sludge generation, high chemical costs, and regular membrane fouling during application are just a few of the most visible disadvantages. On this note, the current study synthesizes magnetite (Fe3O4) nanoparticles using high energy ball milling (HEBM) technique. The Nano-Fe3O4 sorbents were characterized based on scanning electron microscopy (SEM) structure, elemental composition (EDX), surface area analysis (BET), crystallinity (XRD), and functional group analysis (FTIR). The resultant sorbent was coated onto a plastic ball using epoxy resin. The nano-magnetite has multifunctional properties such as superior superparamagnetism, a larger surface area, and is non-toxic. Despite the adsorption ability of Fe3O4, there is little information on its use in removing boron from scheduled waste leachate. Optimization on the application of the sorbent was conducted using the response surface methodology (RSM) to determine the optimum dosage, pH, and contact time for boron removal. Based on the optimization studies, the plastic coated sorbent was applied to the hybrid system comprising of three compartments, namely adsorption, settling, and membrane compartment. Initially, at the adsorption section of the hybrid system, the leachate was subjected adsorption process for 250 minutes, using nano-magnetite coated onto the plastic ball as a sorbent. The remedied effluent was examined, and a considerable performance was noticed in the removal efficiencies of boron, turbidity, copper, and zinc with 74.39 %, 77.26%, 94.21%, and 89.62% at 250 minutes contact time, respectively. Though, the (plastic ball coated sorbent) was able to achieve 74.39% boron removal and 2.2 mg/L concentration. However, this concentration is still above the WHO/EU/DOE (0.5-1.0 mg/L) standard limit. Application of further treatment process became imperative to meet the standard discharge limit. On this note, the PBS treated effluent was transferred to the membrane compartment for further polishing. A nano TiO2 was incorporated into the PVDF-PVD dope to improve the hydrophilicity properties and develop a negatively charge zeta potential on the membrane surface. The formulations encompass different loadings of Nano-TiO2 (0, 0.5, 1.0, 1.5 and 2.0 wt%), and the developed dopes were flipped using phase inversion techniques. The resultant membranes were characterized. The rejection performance was evaluated based on the boron removal from the leachate. PVDF-PVP with 1.0 wt% loading has proven to be the most hydrophilic with 50.01° contact angle alongside with 223.93 L/m2.h and 96.56 L/m2.h permeability flux for pure water and leachate. Despite the potential of TiO2 nanoparticles to improve its hydrophilic properties, information on the application of modified hybrid nano PVDF-polyvinyl pyrrolidone (PVP) for boron separation from SWL remains very scarce. In the wake of the optimum performance of 1.0 wt% TiO2 composite membrane, it was selected and incorporated into the PBS-treated Leachate hybrid system for further polishing. The physicochemical analysis of the treated SWL by the hybrid system revealed that the boron concentration was reduced to 2.2 mg/L at the adsorption compartment. Furthermore, the membrane compartment significantly reduced the boron concentration to 0.43 mg/L, which is far lower than the discharge limit of 1.0 mg/L stipulated by WHO. Finally, the modified hybrid TiO2 membrane has demonstrated to be effective in relegating boron and other contaminants from schedule waste leachate.